Вплив водного колоїдного розчину фулерену С60 на стан мембран та біохімічні показники in vivo - Власов, О.О.; Панов, С.І.; Ковальов, Г.О.; Бєлочкіна, І.В.; Ніпот, О.Є.; Шпакова, Н.М.; Єфімова, І.О.; Сандомирський, Б.П. (39th Annual Conference of Young Scientists ‘Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnology’ May 20–21, 2015, Kharkov, Ukraine. Проблеми кріобіології і кріомедицини. – 2015 – т.25, №2. – С. 195., 2015)
One of the actual tasks in modern nanobiotechnologyis a targeted use of biocompatible nano-sized materials. Theprospects of fullerene application in medicine are associatedwith their high antioxidant activity. The activation of freeradical processes plays a strong negative role in damagingbiological objects after exposure to low temperatures. There-fore the use of fullerenes at the stages of bioobject cryo-preservation may be promising. Taking into account theproperties of fullerenes we may envisage their coming intoa recipient’s body with a transplant. However, the data onfullerene toxicity is now controversial.The research aim was to study the effect of intraperi-toneal administration of aqueous colloidal solution of C60fullerene on visco-elastic properties of erythrocyte membra-nes, as well as on biochemical markers of hepatotoxicity inrats.We injected C60 in 1 mg/kg dose at the concentrationsof 34.7 μmol/l (group 1) and 173 μmol/l (group 2). An osmoticfragility of erythrocytes in hypotonic NaCl solutions (40–100 mmol/l) was studied in 1 and 5 days. The concentrationsof aspartate aminotransferase (AsT), alanine aminotrans-ferase (AlT), alkaline phosphatase (AP) were examined inblood serum.When studying the erythrocyte sensitivity to hypotonyin a day after administering C60 an increased hemolysislevel by 30–60% in 70 mmol/l and 60 mmol/l NaCl solutionswas noted in both groups. To day 5 in the group 1 this indexwas similar to day 1 of observation, but in group 2 it reducedin 60 mmol/l NaCl and 70 mmol/l NaCl solutions by 20% anddown to the control level, respectively. In group 1 the AsTand AlT activity in a day after C60 administration increasedin 1.9 and 1.8 times, respectively, the AP content remainedunchanged. After 5 days the activity of analysed enzymesin this group corresponded to the control level. In group 2all the studied biochemical indices did not differ from thecontrol.Thus, an intraperitoneal administration of C60 in bothconcentrations affects the visco-elastic properties oferythrocyte membranes, by increasing their sensitivity tohypotony. When using C60 in 34.7 μmol/l concentrationthere was revealed its moderate short-term hepatotoxiceffect.We thank Prof. Prylutsky Yu.I. (Taras Shevchenko Kyiv NationalUniversity, Ukraine) for providing aqueous colloidal solutions ofC60 fullerene.
In Vivo Study of Effect of C60 Fullerene Aqueous Colloidal Solutionon Membane State and Biochemical Indices
Власов ОО, Панов СІ , Ковальов ГО, Бєлочкіна ІВ, Ніпот ОЄ, Шпакова НМ, Єфімова ІО, Сандомирський БП. Вплив водного колоїдного розчину фулерену С60 на стан мембран та біохімічні показники in vivo. У: 39th Annual Conference of Young Scientists ‘Cold in Biology and Medicine. Current Issues inCryobiology, Transplantology and Biotechnology’ May 20–21, 2015, Kharkov, Ukraine. Проблеми кріобіології и кріомедицини. 2015; 25(2): с.195.
Keywords: еритроцити щурів; фулерен С60; біохімічні показники; гіпотонічний гемоліз